A management framework for the implementation of policies for industrial ecology, Part I. (18th October 2006) - Indrianti, Nur; Matsuoka, Shinobu; Muraki, Masaaki
This paper discusses the implementation of environmental policy, in particular tax and subsidy policy, that promotes secondary material converted from industrial waste as a substitute for virgin material. We describe a management framework for policy processes that effectively deals with uncertainties and risks arising from implementing the policy. The framework proposes a feedback strategy and cooperation between players involved in the policy, in particular the government and secondary material producers. Cooperation results when secondary material producers are selected. Selection is through a bidding process predicated on price and environmental criteria that will enhance the production of competitive secondary material and lead to realising sustainable industrial ecology.